Evaluation of the condition of high jumpers' locomotor system in the prevention of health problems - Langer, F.; Langerova, A. (Kinesiology, 2008)
The ability to resist a high level of physical strain is very demanding for the condition and function of the support-locomotor system and is a prerequisite for successful coping with the complex locomotor structure of the event and sports training demands. The current condition of first-rate high jumpers` (N=47) locomotor system has been investigated using a questionnaire and information gathered in controlled interviews with contestants, coaches and sports physicians. Based on the occurrence of jumpers` locomotor system injuries the obtained data have been divided into seven parts (foot, shank, knee, thigh, pelvis, trunk and other) and evaluated statistically. Based on the findings, most male and female jumpers` locomotor system injuries were caused by one or a combination of two and more factors, e.g. high values of forces in the course of take-off, a great number of jumps in conjunction with an inappropriate fitness training, wrong technique or anatomical disposition to injuries. The take-off leg, Achilles tendon, take-off leg knee, pelvis and the lumbar part of the spinal column can be considered to be the critical parts of the locomotor system of high jumpers.